Synergistic effect of plant growth promoting rhizobacteria and cirsium arvense against black scurf disease of potato - Zohaib, Karamat Ali; Bashir, Uzma; Khan, Iqra Haider; Javaid, Arshad; Anwar, Waheed (Penerbit Universiti Kebangsaan Malaysia, 2024)
Potato (Solanum tuberosum L.) is an important cash crop of Pakistan. Black scurf of potato is a very important disease that is caused by Rhizoctonia solani Kühn. In this study, management of black scurf of potato was done through biocontrol method by using plant growth promoting rhizobacteria (PGPR) and dry biomass of a weed, Cirsium arvense (L.) Scop. In vitro antagonistic interactions were carried out to assess the potential of two strains of PGPR namely Bacillus megaterium ZMR6 and Pseudomonas fluorescence PF180 against the fungal growth. P. flourescens showed marked antagonistic activity causing 65% reduction in growth of the fungus as compared to 43% reduction due to B. megaterium. Likewise, in laboratory bioassays, methanolic extract of 2, 4 and 6% concentrations of leaf, stem, and root of C. arvense reduced biomass of R. solani by 64-71%, 42-53% and 26-47%, respectively. In pot experiment, the two PGPR species and different doses of C. arvense dry biomass (CDB) viz. 1, 2 and 3% (w/w) were used as soil amendment separately as well as in combination to control the disease. There were 13 treatments, which included a negative control; a positive control (R. solani only); 1, 2 and 3% CDB (separately) together with R. solani, two PGPR species (separately) plus R. solani; different combinations of two PGPR species and CDB together with R. solani. Potato variety Sante was used as test plant. The highest disease incidence (91%) and disease severity (rating scale 4) were observed in positive control (with R. solani only). R. solani significantly reduced biomass of tubers by 52% over negative control. All the treatments significantly enhanced tuber biomass by 18-166% over positive control. The best combination was 3% CDB + P. florescence where minimum disease incidence (3%) and severity (mean disease rating 0.2) were recorded. This treatment also showed the highest tubers yield that was 29% and 166% higher as compared to negative and positive control treatments, respectively. It concluded that P. florescence in combination with 3% dry biomass of C. arvense can control black scurf disease and enhance potato yield.